Founders’ Creativity, Business Model Innovation, and Business Growth - Li, Yang; Li, Beiwei; Lu, Tianhao (Frontiers in Psychology, 2022)
Given the existing research on the role of different founders’ personalities in the growth of new ventures, we take the digital technology start-ups as the research object and focus on the role of the founder’s creativity. In this research, we assess the relationship between founders’ creativity and business growth. Based on social cognition theory and upper echelons theory, we propose several research hypotheses. Using a sample of 153 new ventures in the Chinese transitional economy, we find that both founders’ creativity and business model innovation have positive impacts on enterprise growth. We also examine whether business model innovation mediates the effects of founder’s creativity on enterprise growth. The results show that business model innovation positively mediates the relationship between founders’ creativity and enterprise growth. The conclusion of our analysis helps the founders to innovate through business models and unleash individual creativity to promote the potential of the rapid growth of enterprises.